Gender Equality in Rural Africa: From Commitments to Outcomes - Quisumbing, Agnes R.; Meinzen-Dick, Ruth S.; Njuki, Jemimah (2019)
Agnes Quisumbing, Ruth Meinzen-Dick, and Jemimah Njuki POLICY SEMINAR Gender Equality in Rural Africa: From Commitments to Outcomes Co-Organized by the Regional Strategic Analysis and Knowledge Support System (ReSAKSS) and IFPRI DEC 12, 2019 - 12:15 PM TO 01:45 PM EST